2020
DOI: 10.3390/ijms21207747
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Hydrogen Exchanger Regulatory Factor-1 (NHERF1) Regulates Fetal Membrane Inflammation

Abstract: The fetal inflammatory response, a key contributor of infection-associated preterm birth (PTB), is mediated by nuclear factor kappa B (NF-kB) activation. Na+/H+ exchanger regulatory factor-1 (NHERF1) is an adapter protein that can regulate intracellular signal transduction and thus influence NF-kB activation. Accordingly, NHERF1 has been reported to enhance proinflammatory cytokine release and amplify inflammation in a NF-kB-dependent fashion in different cell types. The objective of this study was to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 79 publications
(94 reference statements)
0
17
0
Order By: Relevance
“…The collection of placentas was approved by the Institutional Review Board (IRB) at the University of Texas Medical Branch (UTMB) at Galveston, TX (IRB approval number IRB16.0058, January 2020). The protocol allows for the collection of discarded placentas from term vaginal or term, not in labor, cesarean deliveries (TL and TNIL, respectively) from John Sealy Hospital according to our laboratory's inclusion and exclusion criteria as described in previous reports [13,14]. The protocol is exempt from subject consent as the specimens are non-identifiable and were intended to be discarded.…”
Section: Tissue Collection and Institutional Review Board Approvalmentioning
confidence: 99%
See 1 more Smart Citation
“…The collection of placentas was approved by the Institutional Review Board (IRB) at the University of Texas Medical Branch (UTMB) at Galveston, TX (IRB approval number IRB16.0058, January 2020). The protocol allows for the collection of discarded placentas from term vaginal or term, not in labor, cesarean deliveries (TL and TNIL, respectively) from John Sealy Hospital according to our laboratory's inclusion and exclusion criteria as described in previous reports [13,14]. The protocol is exempt from subject consent as the specimens are non-identifiable and were intended to be discarded.…”
Section: Tissue Collection and Institutional Review Board Approvalmentioning
confidence: 99%
“…Our recent data showed that fetal membranes (FMs-amniochorion), along with the placenta, express various transport proteins; however, their localization within FM cells and functions have not yet been elucidated. Since human fetal membranes are involved in various protective mechanisms [11][12][13][14][15][16] during pregnancy, it is likely that transport protein functions may also be controlled by the FMs. Determining the role of FMs in drug transport is necessary and could lead to a greater understanding of pharmacokinetics in pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry (IHC) for OATP2B1 was performed on FM tissues using methods previously described by our laboratory (Kammala et al, 2020). Briefly, FM sections were fixed in 4% paraformaldehyde for 48 h and embedded in paraffin.…”
Section: Immunohistochemistry For Oatp2b1mentioning
confidence: 99%
“…33 Maternal decidual and FM cells were cultured as previously described. 34,28,35 The cells used for all experiments were within 10 passages.…”
Section: Maternal Decidual and Fm Cells (Amnion Epithelial Cells [Aecs] Amnion Mesenchymal Cells [Amcs] Chorionic Trophoblast Cells [Ctcsmentioning
confidence: 99%
“…Small interfering RNA-mediated knockdown of NHERF1 in BeWo cells and CTCs Small interfering RNA (siRNA) On-Target plus smart pool oligos (Dharmacon, Lafayette, CO, USA) directed against NHERF1 or nontarget scrambled (NT; control) siRNA was used to transfect FMs cells (AECs, AMCs, CMCs, and CTCs) using the RNAimax lipofectamine reagent as previously described. 28 Twenty-four hours after transfection, the cells were used for subsequent assessment of protein expression and stimulation.…”
Section: 10mentioning
confidence: 99%